2006
DOI: 10.1038/sj.onc.1210156
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-1 plays a role in suppressing mammary tumourigenesis in mice

Abstract: The DNA strand break-binding molecule, poly(ADPribose) polymerase-1 (PARP-1), plays a role in DNA repair, chromosomal stability, transcription and cell death. Accumulating evidence suggests that dysfunction of PARP-1 contributes to tumorigenesis. Here, we report that PARP-1 deficiency causes mammary carcinoma formation in female mice, and that the introduction of Trp53 mutations accelerates the onset and shortens the latency of mammary tumorigenesis. We show that PARP-1 deficiency results in chromosomal aneupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 43 publications
2
41
0
1
Order By: Relevance
“…These data suggest a synergistic interaction between Parp-2 and p53 in the maintenance of genome integrity, resulting in accelerated tumorigenesis when both genes are disrupted in mice (Figure 3b). Parp-1 deficiency has also been shown to shorten the latency of tumour development in p53 À/À mice (Beneke and Mo¨ro¨y, 2001;Tong et al, 2001Tong et al, , 2003Tong et al, , 2007. However, Parp-1 deficiency in mice, in contrast to Parp-2 deficiency, did not affect either thymocyte development (Yelamos et al, 2006) or thymocyte apoptosis in response to different stimuli (Wang et al, 1997).…”
Section: Cd8mentioning
confidence: 91%
See 1 more Smart Citation
“…These data suggest a synergistic interaction between Parp-2 and p53 in the maintenance of genome integrity, resulting in accelerated tumorigenesis when both genes are disrupted in mice (Figure 3b). Parp-1 deficiency has also been shown to shorten the latency of tumour development in p53 À/À mice (Beneke and Mo¨ro¨y, 2001;Tong et al, 2001Tong et al, , 2003Tong et al, , 2007. However, Parp-1 deficiency in mice, in contrast to Parp-2 deficiency, did not affect either thymocyte development (Yelamos et al, 2006) or thymocyte apoptosis in response to different stimuli (Wang et al, 1997).…”
Section: Cd8mentioning
confidence: 91%
“…Among the 17 members of the Parp family, Parp-1 (113 kDa) and Parp-2 (62 kDa) are so far the only Parp enzymes whose catalytic activity has been shown to be stimulated by DNA strand interruptions, targeting proteins mainly involved in chromatin structure and DNA metabolism Yelamos et al, 2008). Whereas Parp-1-deficient (Parp-1 À/À ) mice develop spontaneous mammary and liver tumours with long latency and at a low incidence (Tong et al, 2002(Tong et al, , 2007, Parp-2 À/À mice do not show the propensity for development of spontaneous tumours (Menissier et al, 2003). However, both Parp-1 À/À mice and Parp-2 À/À mice are very sensitive to ionizing radiation and alkylating agents, thus suggesting a role for these proteins in the cellular response to DNA damage and genomic stability through their physical association with, or by the poly(ADPribosyl)ation of their partner proteins (Menissier et al, 2003).…”
mentioning
confidence: 99%
“…Some phenanthrene-derived poly-ADP-ribose polymerase (PARP) inhibitors also exhibit cancer cell-specific declustering. 134 PARP-1 expression is upregulated in various human cancers 135 but downregulated in others, 136 suggesting a complex role for this protein in tumorigenesis. Treatment of tumors exhibiting centrosome amplification with the phenanthrene-derived PARP-1 inhibitor, PJ-34, results in clustering inhibition, spindle multipolarity, and death by mitotic catastrophe.…”
Section: Disperse and Destroy: Induction Of Spindle Multipolarity As mentioning
confidence: 99%
“…However, PARP-1 has been implicated in centrosome amplification. 136 Furthermore, in their screen for clustering proteins in S2 cells, Kwon et al 6 identified a PARP, tankyrase-1, and a putative PARP-16 homolog as molecules critical for clustering. Considering that PARP-1 inhibitors induce declustering, these drugs evince great potential for cancer cell-specific chemotherapy.…”
Section: Disperse and Destroy: Induction Of Spindle Multipolarity As mentioning
confidence: 99%
“…And, the potential for secondary cancers to occur through genomic instability from inhibition of PARP-1 is possible. In an in vivo study of PARP-1 deficiency, female mice developed mammary carcinoma (Tong, Yang et al 2007); (Drew and Plummer). Furthermore, secondary mutations after PARP inhibitor treatment may lead to drug resistance.…”
Section: Clinical Implications Of Parp Inhibitor Usementioning
confidence: 99%